INTERDEPENDENCE BETWEEN OFFICIAL DEVELOPMENT AID AND MACROECONOMIC INDICATORSOF COUNTRIES WITH EMERGING MARKETS (Вісник: Міжнародні відносини, 2021)
International development aid is the voluntary transfer of funds in the form of goods, skills, grants, credits and loans, training, exchange of experience from donor countries to recipients of these funds. Alongside with the aid in the traditional sense, other factors are also important, such as trade, migration, investment, environment, security, technology, i.e., everything that constitutes the development strategy and has a significantimpact on it. Official development aid is aimed at rebuilding infrastructure, institutions and promoting the economic development of countries, which is a key part of post-war peace agreements. Official development aid (ODA) increases investment in physical and human capital, the ability to import capital goods or technology. ODA does not have indirect effects that reduce investment rates or savings, but is associated with the transfer of technologies that increase capital productivity and promote endogenous technical changes.Among a wide range of funding sources, official development aid plays an important role. It helps launch projects in underdeveloped or underfunded sectors or domains. ODA initiates processes of "virtuous development" and creates favourable dynamics that can help involve all other parties, especially business representatives, in such projects. This creates a multiplier effect that multiplies the impact. It was discovered during the research that official development aid increases investment in physical and human capital, the ability to import capital goods or technology. ODA does not have indirect effects that reduce investment rates or savings but relates to the transfer of technologies that increase capital productivity and promote endogenous technical changes. A study of the impact of official development aid on economic growth and poverty in the 20 countries studied showed that in most countries there was a negative correlation between the indicators of official development aid and gross domestic product, only a few countries showed a positive relationship between the two variables at a high level. The same situation can be observed between ODA and the poverty line. The relationship between the two variables that are not related to the provision of official development aid shows the best result, but ODA does not affect them. This analysis confirmed the theoretical and empirical research of scientists in this field on the lack of connection or weak connection between the studied variables. However, Student's t-test analysis indicates that there is a close relationship between GDP and ODA, as confirmed by the results of the study.
Keywords: official development aid, international technical assistance, humanitarian aid, emerging market, international organizations, economic-mathematical modeling, Student's t-test.